2019
DOI: 10.1016/j.gie.2019.04.234
|View full text |Cite
|
Sign up to set email alerts
|

ASGE guideline on the role of endoscopy for bleeding from chronic radiation proctopathy

Abstract: Chronic radiation proctopathy is a common sequela of radiation therapy for malignancies in the pelvic region. A variety of medical and endoscopic therapies have been used for the management of bleeding from chronic radiation proctopathy. In this guideline, we reviewed the results of a systematic search of the literature from 1946 to 2017 to formulate clinical questions and recommendations on the role of endoscopy for bleeding from chronic radiation proctopathy. The following endoscopic modalities are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 61 publications
1
38
0
2
Order By: Relevance
“…Other treatments include formalin application (which has coagulative properties) and endoscopic interventions, including argon plasma coagulation. It is prudent to proceed conservatively in these situations, as there is a chance of iatrogenic fistula formation with aggressive interventions 133,134 …”
Section: Gastrointestinalmentioning
confidence: 99%
“…Other treatments include formalin application (which has coagulative properties) and endoscopic interventions, including argon plasma coagulation. It is prudent to proceed conservatively in these situations, as there is a chance of iatrogenic fistula formation with aggressive interventions 133,134 …”
Section: Gastrointestinalmentioning
confidence: 99%
“…1 A pooled analysis revealed that APC had a high overall success rate of 87%, with a mean or median number of treatment sessions ranging from 1-3.7. 5 However, in patients who received high-dose RT, the impaired recovery of the rectum after APC might worsen the bleeding. Canard et al found that three (10%) patients had severe complications after APC (i.e., extensive rectal necrosis, perforation, and severe bleeding).…”
Section: Discussionmentioning
confidence: 99%
“…Die Gabe von 2 verschiedenen Antibiotika ist wegen zunehmender (Penicillin-)Resistenzen empfohlen, eine PCR kann bei symptomlosen Patienten zuverlässigere Ergebnisse liefern als die Kultur allein [15]. chirurgische Übernähung bis hin zur Proktektomie) -was nicht selten zur vermehrten Fibrosierung beiträgt und den funktionellen Aspekt der Erkrankung verschlechtern kann [27,28,29]. Auch zu bedenken ist: Ein invasives Vorgehen ist aufgrund des fragilen Gewebes und nicht zuletzt wegen der Komorbiditäten der Patienten mit einem relevanten Komplikationsrisiko verbunden und zielt als Therapieansatz nur auf das Symptom der Hämorrhagien [30].…”
Section: Bakterielle Erregerunclassified
“…In den Empfehlungen der American Society of Colon and Rectal Surgeons (ASCR; [34]) und der American Society for Gastrointestinal Endoscopy (ASGE; [28]) werden für die hämorrhagische Strahlenproktitis ein endoskopisches Vorgehen (vor allem mit Argonplasmakoagulation) und der topische Off-label-Gebrauch von Formalin empfohlen, im Weiteren auch Sucralfateinläufe oder hyperbarer Sauerstoff -allesamt mit moderater Evidenz. In der Literatur wird auch darauf hingewiesen, dass über aktuelle Therapieoptionen (vor allem für die hämorrhagische Komponente) nach Vorhandensein von Möglichkeiten und Expertise entschieden wird.…”
Section: Bakterielle Erregerunclassified